Effectiveness of Gentle Human Touch for Pain Control During Examination for Retinopathy of Pre-maturity: A Randomized Controlled Trial - Sun, Yongping; Zhang, Jinghan; Chen, Xu; Yang, Yang; Qiu, Jie; Lu, Ke-yu; Cheng, Rui (Frontiers in Pediatrics, 2020)
Retinopathy of prematurity (ROP) is a disorder of the retinal blood vessels in preterm infants with low birth weight. It is a leading cause of blindness in children. During ROP screening, the use of mydriatic drops and eyelid openers causes pain and discomfort. Touch intervention is frequently provided to relieve procedural pain in neonates. The objectives of this study was to investigate the effects of touch intervention on pain in preterm infants undergoing screening for ROP. In this randomized controlled trial, 66 infants in the neonatal intensive care unit at Children’s Hospital of Nanjing Medical University who met the ROP screening criteria were randomly assigned to experimental and control groups using computer-generated randomization codes. Neonatologists, parents, and researchers were blinded to the randomization. The infants in the experimental group continuously received touch intervention during screening, while those in the control group were screened according to the routine procedure. All neonates were administered local eye anesthesia before the screening. The degree of pain was assessed using the Premature Infant Pain Profile score. A double-channel near-infrared spectroscopy device was used to monitor regional cerebral oxygen saturation (rScO2), while oxygen saturation (SaO2) and heart rate were measured using pulse oximetry. The Premature Infant Pain Profile score was the primary outcome, while heart rate, SaO2, and rScO2 were the secondary outcomes.